Stain resistant yarns and carpets made with stain resistant yarns
Patent Information
- Application Number
- CN202310766238.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-27
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-06-27
AI Technical Summary
[0004]目前市面上的PA6耐污地毯大多是在地毯表层涂覆耐污涂层,价格偏高,地毯深层纱线缺少耐污功能,清洗地毯过后,耐污效果会大打折扣,因此考虑设计一种持续长效耐污的地毯,使其能够具有较好的酸性耐污性能;鉴于此,我们提出耐污纱线及利用耐污纱线制成的地毯
[0043]This stain-resistant yarn and carpets made from it reduce the number of amino groups in the PA6 material macromolecular chain by adding modified functional masterbatch, forming covalent bonds with the amino groups. This prevents the amino groups from attracting negatively charged pollutants. At the same time, the amino groups in the modified functional masterbatch are blocked, slowing down or preventing the chemical reaction and binding with hydroxyl groups in acidic liquids. This effectively prevents the adsorption of acidic and negatively charged pollutants, allowing for direct rinsing and easy separation of pollutants. The yarn manufacturing process controls the screw extrusion temperature and expansion deformation temperature to maintain the yarn's mechanical strength. In addition, perfluorooctane and silicone oil can be incorporated into PA6 to obtain uniform hydrophobicity, preventing liquid pollutant corrosion. Heptadecafluorooctane-1-sulfonic acid has strong hydrophobicity and can provide sulfonic acid groups. With high electronegativity, it can repel negatively charged pollutants and form a hydrophobic layer. The synergistic effect of these components can modify the structure and hydrophobicity of PA6, respectively. Carpets made from this yarn have good acid stain resistance and resistance to negatively charged pollutants.
Smart Images

Figure BDA0004306282920000011 
Figure BDA0004306282920000021 
Figure BDA0004306282920000051
Abstract
Description
Technical Field
[0001] This invention relates to the field of automotive and civilian carpet yarn technology, specifically to stain-resistant yarn and carpets made from stain-resistant yarn. Background Technology
[0002] Carpets have become standard equipment on cars of all brands. They are not only aesthetically pleasing and comfortable, but also absorb noise from the engine and chassis, provide insulation and dust absorption. In addition, carpets are inexpensive and easy to produce, so they occupy the majority of the market share.
[0003] Most car carpets on the market are currently made of PA6 material. PA6 has excellent wear resistance, a long service life, good resilience, and a comfortable feel. However, as the bottom layer of the car interior structure, carpets inevitably accumulate dust and dirt. Furthermore, due to the seats, they are difficult to clean thoroughly and frequently. If acidic liquids such as red wine or tomato sauce are spilled inside the car, the seats must be removed, and the carpet wiped clean with a special cleaner and allowed to dry. Otherwise, the carpet may mold, leading to rust on the car floor and reducing the car's lifespan. Therefore, improving the stain resistance of carpets is a problem that carpet manufacturers urgently need to solve.
[0004] Most PA6 stain-resistant carpets on the market today have a stain-resistant coating on the surface, which is relatively expensive. The deep yarns of the carpet lack stain resistance, and the stain resistance is greatly reduced after cleaning. Therefore, we are considering designing a long-lasting stain-resistant carpet with good acid stain resistance. In view of this, we propose stain-resistant yarn and carpets made from stain-resistant yarn. Summary of the Invention
[0005] To overcome the above deficiencies, the present invention provides stain-resistant yarn and carpets made from stain-resistant yarn.
[0006] The technical solution of this invention is:
[0007] The stain-resistant yarn includes a base material of PA6, and other components are added to the yarn. The specific mass ratio of the other components to PA6 is as follows:
[0008]
[0009]
[0010] It is important to explain that both perfluorooctane and heptadecafluorooctane-1-sulfonic acid are fluorocarbon compounds with electronegativity and low surface energy. Based on the principle of like charge repulsion, they can prevent the adsorption of negatively charged pollutants. In addition, when blended in PA6, they can uniformly form a hydrophobic layer, making it difficult for liquids, including acidic liquids, to penetrate, thus helping to maintain good stain resistance. At the same time, the hydrophobic groups of silicone oil can also form a hydrophobic layer, achieving stable hydrophobicity. Furthermore, heptadecafluorooctane-1-sulfonic acid also acts as a medium or in multiple ways. It contains sulfonic acid groups that can form covalent bonds with the amino groups in PA6 material, reducing the number of amino groups that can react with carboxyl groups in acidic liquids, thereby improving its stain resistance.
[0011] Preferably, the modified functional masterbatch preparation components include PA6 raw material, and 45-55% sulfonic acid, 40-50% acrylic acid and 40-50% benzamide, which account for 45-55% of the molar mass of PA6 raw material.
[0012] Preferably, in the preparation process of the modified functional masterbatch, sulfonic acid and acrylic acid are dissolved in water, and benzamide is dissolved in ethanol solution, all to prepare sulfonic acid solution, acrylic acid solution, and benzamide ethanol solution with a concentration of 3-5%.
[0013] Preferably, the specific process for preparing the modified functional masterbatch is as follows:
[0014] Step 1: Add PA6 to a 3-5% sulfonic acid solution, add trisodium phosphate or ammonium sulfate as a catalyst, control the reaction temperature at 80-100℃, and react for 2-4 hours;
[0015] Step 2: After filtration, wash with clean water and dry, add to a 3-5% acrylic acid solution, control the reaction temperature at 100-120℃, and react for 1-2 hours;
[0016] Step 3: After filtering again, wash with clean water and dry. Add to a 3-5% concentration of benzamide ethanol solution, control the reaction temperature at 60-70℃, seal and pressurize at 1.2-1.8MPa, and react for 1-2 hours.
[0017] Step 4: After filtration, rinse with clean water and dry for later use.
[0018] Preferably, the chemical equation for the reaction in step one is:
[0019] NH2-R-NH-CO(CH2)5-COOH+HOOC-CH2-CH2-SO3H→NH2-R-NH-CO(CH2)5-COO-SO3H+H2O
[0020] Wherein: NH2-R-NH-CO(CH2)5-COOH is PA6; HOOC-CH2-CH2-SO3H is sulfonic acid.
[0021] It should be noted that both the sulfonic acid solution and heptadecafluorooctane-1-sulfonic acid have sulfonic acid groups, but the reaction conditions here are different. By adding a catalyst and controlling the temperature, the sulfonic acid groups are directed to undergo an amidation reaction with nylon 6 to generate sulfonic acid nylon 6. Obtaining amide bonds can improve the durability and strength of the material, which is beneficial to improving mechanical strength.
[0022] Preferably, the chemical equation for the reaction in step two includes:
[0023] CH2=CH-COOH+NH2-R-NH-CO(CH2)5-COOH→CH2=CH-CONH-R-NH-CO(CH2)5-COOH+H2O
[0024] or:
[0025] CH2=CH-COOH+NH2-R-NH-CO(CH2)5-COO-SO3H→CH2=CH-CONH-NH2-R-NH-CO(CH2)5-COO-SO3H+H2O
[0026] Wherein: NH2-R-NH-CO(CH2)5-COOH is PA6; CH2=CHCOOH is acrylic acid.
[0027] It should be noted that the reactive group here is the combination of the carboxyl group and the amino group in acrylic acid. The sulfonic acid nylon 6 generated in step one also contains amino groups. Therefore, this step can combine amino groups, reduce the number of amino groups, form closed amino groups, and avoid chemical reactions with acidic pollutants in the later stage.
[0028] Preferably, the reaction chemical equation for step three includes:
[0029] C6H5-CONH2+NH2-R-NH-CO(CH2)5-COOH→C6H5-CONH-R-NH-CO(CH2)5-COOH+NH3↑
[0030] or:
[0031] C6H5-CONH2+NH2-R-NH-CO(CH2)5-COO-SO3H→C6H5-CONH-R-NH-CO(CH2)5-COO-SO3H+NH3↑
[0032] Wherein: NH2-R-NH-CO(CH2)5-COOH is PA6; C6H5-CONH2 is benzamide.
[0033] It is important to note that the reactive group here is the combination of the amide group in benzamide and the amino group. Step two cannot fully combine the amino groups in sulfonated nylon 6 and PA6. Therefore, this step can further combine the amino groups, thereby blocking the number of amino groups and preventing chemical reactions from occurring when in contact with acidic pollutants later. Benzamide and acrylic acid provide different binding groups, which work synergistically to achieve a reinforcing effect.
[0034] Preferably, the specific steps in the preparation process of the stain-resistant yarn are as follows:
[0035] Step 1: Mix the prepared components into the hopper according to the proportions and stir until homogeneous. Use a screw extruder for melt extrusion and control the screw temperature settings as follows: 245℃, 285℃, 275℃, 273℃, 270℃, 268℃, 265℃.
[0036] Step 2: The extruded material is spun through the spinneret in the spinning box, cooled by side blowing air, bundled and oiled, and the oil pump is controlled to apply oil at 25-35%;
[0037] Step 3: Pre-network, set the pre-network pressure to 1.5-1.8 bar;
[0038] Step 4: Traction, control the ratio of the speed of the double roller to the speed of the single roller to be 2.28-2.35;
[0039] Step 5: After expansion and deformation, cool and wind the coil, controlling the winding speed to be 2520-2550 m / min.
[0040] Preferably, the temperature of the expansion deformation control roller is 185-190℃, the temperature of the deformer is 198-200℃, and the deformation pressure is set to 7.4-7.6 bar.
[0041] A carpet made of stain-resistant yarn, which can be woven using a shuttle loom.
[0042] Compared with the prior art, the beneficial effects of the present invention are:
[0043] This stain-resistant yarn and carpets made from it reduce the number of amino groups in the PA6 material macromolecular chain by adding modified functional masterbatch, forming covalent bonds with the amino groups. This prevents the amino groups from attracting negatively charged pollutants. At the same time, the amino groups in the modified functional masterbatch are blocked, slowing down or preventing the chemical reaction and binding with hydroxyl groups in acidic liquids. This effectively prevents the adsorption of acidic and negatively charged pollutants, allowing for direct rinsing and easy separation of pollutants. The yarn manufacturing process controls the screw extrusion temperature and expansion deformation temperature to maintain the yarn's mechanical strength. In addition, perfluorooctane and silicone oil can be incorporated into PA6 to obtain uniform hydrophobicity, preventing liquid pollutant corrosion. Heptadecafluorooctane-1-sulfonic acid has strong hydrophobicity and can provide sulfonic acid groups. With high electronegativity, it can repel negatively charged pollutants and form a hydrophobic layer. The synergistic effect of these components can modify the structure and hydrophobicity of PA6, respectively. Carpets made from this yarn have good acid stain resistance and resistance to negatively charged pollutants. Detailed Implementation
[0044] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0045] The present invention will describe the above technical solution in detail through the following embodiments:
[0046] Example 1
[0047] Stain-resistant yarn, including yarn using PA6 as the matrix material, also contains other components. The specific mass ratio of these other components to PA6 is as follows:
[0048]
[0049] The modified functional masterbatch preparation components include PA6 raw material, and 55% sulfonic acid, 50% acrylic acid and 50% benzamide, which account for 55% of the molar mass of PA6 raw material, are weighed out for later use.
[0050] In the preparation of the modified functional masterbatch, sulfonic acid and acrylic acid are first fully dissolved in water, and benzamide is dissolved in ethanol solution to prepare a 5% sulfonic acid solution, acrylic acid solution, and benzamide ethanol solution.
[0051] The specific process for preparing modified functional masterbatch is as follows:
[0052] Step 1: First, add PA6 to a 5% sulfonic acid solution, add trisodium phosphate as a catalyst, control the reaction temperature at 95℃, and react for 2.5 hours.
[0053] Step 2: After filtration, wash with clean water and dry, add to a 5% acrylic acid solution, control the reaction temperature at 110℃, and react for 1.5 hours;
[0054] Step 3: After filtering again, wash with clean water and dry, add to a 5% benzamide ethanol solution, control the reaction temperature at 62℃, seal and pressurize at 1.6MPa, and react for 1.5h;
[0055] Step 4: After filtration, rinse with clean water and dry for later use.
[0056] The chemical equation for the reaction in step one is:
[0057] NH2-R-NH-CO(CH2)5-COOH+HOOC-CH2-CH2-SO3H→NH2-R-NH-CO(CH2)5-COO-SO3H+H2O
[0058] Wherein: NH2-R-NH-CO(CH2)5-COOH is PA6; HOOC-CH2-CH2-SO3H is sulfonic acid;
[0059] NH2-R-NH-CO(CH2)5-COO-SO3H represents sulfonic acid nylon 6;
[0060] The chemical equations for the reaction in step two include:
[0061] CH2=CH-COOH+NH2-R-NH-CO(CH2)5-COOH→CH2=CH-CONH-R-NH-CO(CH2)5-COOH+H2O
[0062] or:
[0063] CH2=CH-COOH+NH2-R-NH-CO(CH2)5-COO-SO3H→CH2=CH-CONH-NH2-R-NH-CO(CH2)5-COO-SO3H+H2O
[0064] Wherein: NH2-R-NH-CO(CH2)5-COOH is PA6; CH2=CHCOOH is acrylic acid.
[0065] The chemical equations for the reaction in step three include:
[0066] C6H5-CONH2+NH2-R-NH-CO(CH2)5-COOH→C6H5-CONH-R-NH-CO(CH2)5-COOH+NH3↑
[0067] or:
[0068] C6H5-CONH2+NH2-R-NH-CO(CH2)5-COO-SO3H→C6H5-CONH-R-NH-CO(CH2)5-COO-SO3H+NH3↑
[0069] Wherein: NH2-R-NH-CO(CH2)5-COOH is PA6; C6H5-CONH2 is benzamide.
[0070] The specific steps in the preparation process of stain-resistant yarn are as follows:
[0071] Step 1: Mix the prepared components into the hopper according to the proportions and stir until homogeneous. Use a screw extruder for melt extrusion and control the screw temperature settings as follows: 245℃, 285℃, 275℃, 273℃, 270℃, 268℃, 265℃.
[0072] Step 2: The extruded material is spun through the spinneret in the spinning box, cooled by side blowing, bundled and oiled, and the oil pump is controlled to apply 30% of the oil.
[0073] Step 3: Pre-network, set the pre-network pressure to 1.6 bar;
[0074] Step 4: Traction, control the ratio of the speed of the double rollers to the speed of the single roller to be 2.32;
[0075] Step 5: After expansion and deformation, cool and wind the coil, controlling the winding speed to 2520m / min.
[0076] The expansion deformation control roller temperature is set at 188℃, the deformer temperature at 198℃, and the deformation pressure is set at 7.5 bar.
[0077] This stain-resistant yarn can be used to weave carpets made from stain-resistant yarn using shuttle looms.
[0078] Example 2
[0079] Stain-resistant yarn, including yarn using PA6 as the matrix material, also contains other components. The specific mass ratio of these other components to PA6 is as follows:
[0080]
[0081] The modified functional masterbatch preparation components include PA6 raw material, and 55% sulfonic acid, 50% acrylic acid and 50% benzamide, which account for 55% of the molar mass of PA6 raw material, are weighed out for later use.
[0082] In the preparation of the modified functional masterbatch, sulfonic acid and acrylic acid are first fully dissolved in water, and benzamide is dissolved in ethanol solution to prepare a 5% sulfonic acid solution, acrylic acid solution, and benzamide ethanol solution.
[0083] The specific process for preparing modified functional masterbatch is as follows:
[0084] Step 1: First, add PA6 to a 5% sulfonic acid solution, add trisodium phosphate as a catalyst, control the reaction temperature at 95℃, and react for 2.5 hours.
[0085] Step 2: After filtration, wash with clean water and dry, add to a 5% acrylic acid solution, control the reaction temperature at 110℃, and react for 1.5 hours;
[0086] Step 3: After filtering again, wash with clean water and dry, add to a 5% benzamide ethanol solution, control the reaction temperature at 62℃, seal and pressurize at 1.6MPa, and react for 1.5h;
[0087] Step 4: After filtration, rinse with clean water and dry for later use.
[0088] The chemical equation for the reaction in step one is:
[0089] NH2-R-NH-CO(CH2)5-COOH+HOOC-CH2-CH2-SO3H→NH2-R-NH-CO(CH2)5-COO-SO3H+H2O
[0090] Wherein: NH2-R-NH-CO(CH2)5-COOH is PA6; HOOC-CH2-CH2-SO3H is sulfonic acid;
[0091] NH2-R-NH-CO(CH2)5-COO-SO3H represents sulfonic acid nylon 6;
[0092] The chemical equations for the reaction in step two include:
[0093] CH2=CH-COOH+NH2-R-NH-CO(CH2)5-COOH→CH2=CH-CONH-R-NH-CO(CH2)5-COOH+H2O
[0094] or:
[0095] CH2=CH-COOH+NH2-R-NH-CO(CH2)5-COO-SO3H→CH2=CH-CONH-NH2-R-NH-CO(CH2)5-COO-SO3H+H2O
[0096] Wherein: NH2-R-NH-CO(CH2)5-COOH is PA6; CH2=CHCOOH is acrylic acid.
[0097] The chemical equations for the reaction in step three include:
[0098] C6H5-CONH2+NH2-R-NH-CO(CH2)5-COOH→C6H5-CONH-R-NH-CO(CH2)5-COOH+NH3↑
[0099] or:
[0100] C6H5-CONH2+NH2-R-NH-CO(CH2)5-COO-SO3H→C6H5-CONH-R-NH-CO(CH2)5-COO-SO3H+NH3↑
[0101] Wherein: NH2-R-NH-CO(CH2)5-COOH is PA6; C6H5-CONH2 is benzamide.
[0102] The specific steps in the preparation process of stain-resistant yarn are as follows:
[0103] Step 1: Mix the prepared components into the hopper according to the proportions and stir until homogeneous. Use a screw extruder for melt extrusion and control the screw temperature settings as follows: 245℃, 285℃, 275℃, 273℃, 270℃, 268℃, 265℃.
[0104] Step 2: The extruded material is spun through the spinneret in the spinning box, cooled by side blowing, bundled and oiled, and the oil pump is controlled to apply 30% of the oil.
[0105] Step 3: Pre-network, set the pre-network pressure to 1.6 bar;
[0106] Step 4: Traction, control the ratio of the speed of the double rollers to the speed of the single roller to be 2.32;
[0107] Step 5: After expansion and deformation, cool and wind the coil, controlling the winding speed to 2530m / min.
[0108] The expansion deformation control roller temperature is set at 188℃, the deformer temperature at 198℃, and the deformation pressure is set at 7.5 bar.
[0109] This stain-resistant yarn can be used to weave carpets made from stain-resistant yarn using shuttle looms.
[0110] Example 3
[0111] Stain-resistant yarn, including yarn using PA6 as the matrix material, also contains other components. The specific mass ratio of these other components to PA6 is as follows:
[0112]
[0113] The modified functional masterbatch preparation components include PA6 raw material, and 55% sulfonic acid, 50% acrylic acid and 50% benzamide, which account for 55% of the molar mass of PA6 raw material, are weighed out for later use.
[0114] In the preparation of the modified functional masterbatch, sulfonic acid and acrylic acid are first fully dissolved in water, and benzamide is dissolved in ethanol solution to prepare a 5% sulfonic acid solution, acrylic acid solution, and benzamide ethanol solution.
[0115] The specific process for preparing modified functional masterbatch is as follows:
[0116] Step 1: First, add PA6 to a 5% sulfonic acid solution, add trisodium phosphate as a catalyst, control the reaction temperature at 95℃, and react for 2.5 hours.
[0117] Step 2: After filtration, wash with clean water and dry, add to a 5% acrylic acid solution, control the reaction temperature at 110℃, and react for 1.5 hours;
[0118] Step 3: After filtering again, wash with clean water and dry, add to a 5% benzamide ethanol solution, control the reaction temperature at 62℃, seal and pressurize at 1.6MPa, and react for 1.5h;
[0119] Step 4: After filtration, rinse with clean water and dry for later use.
[0120] The chemical equation for the reaction in step one is:
[0121] NH2-R-NH-CO(CH2)5-COOH+HOOC-CH2-CH2-SO3H→NH2-R-NH-CO(CH2)5-COO-SO3H+H2O
[0122] Wherein: NH2-R-NH-CO(CH2)5-COOH is PA6; HOOC-CH2-CH2-SO3H is sulfonic acid;
[0123] NH2-R-NH-CO(CH2)5-COO-SO3H represents sulfonic acid nylon 6;
[0124] The chemical equations for the reaction in step two include:
[0125] CH2=CH-COOH+NH2-R-NH-CO(CH2)5-COOH→CH2=CH-CONH-R-NH-CO(CH2)5-COOH+H2O
[0126] or:
[0127] CH2=CH-COOH+NH2-R-NH-CO(CH2)5-COO-SO3H→CH2=CH-CONH-NH2-R-NH-CO(CH2)5-COO-SO3H+H2O
[0128] Wherein: NH2-R-NH-CO(CH2)5-COOH is PA6; CH2=CHCOOH is acrylic acid.
[0129] The chemical equations for the reaction in step three include:
[0130] C6H5-CONH2+NH2-R-NH-CO(CH2)5-COOH→C6H5-CONH-R-NH-CO(CH2)5-COOH+NH3↑
[0131] or:
[0132] C6H5-CONH2+NH2-R-NH-CO(CH2)5-COO-SO3H→C6H5-CONH-R-NH-CO(CH2)5-COO-SO3H+NH3↑
[0133] Wherein: NH2-R-NH-CO(CH2)5-COOH is PA6; C6H5-CONH2 is benzamide.
[0134] The specific steps in the preparation process of stain-resistant yarn are as follows:
[0135] Step 1: Mix the prepared components into the hopper according to the proportions and stir until homogeneous. Use a screw extruder for melt extrusion and control the screw temperature settings as follows: 245℃, 285℃, 275℃, 273℃, 270℃, 268℃, 265℃.
[0136] Step 2: The extruded material is spun through the spinneret in the spinning box, cooled by side blowing, bundled and oiled, and the oil pump is controlled to apply 30% of the oil.
[0137] Step 3: Pre-network, set the pre-network pressure to 1.6 bar;
[0138] Step 4: Traction, control the ratio of the speed of the double rollers to the speed of the single roller to be 2.32;
[0139] Step 5: After expansion and deformation, cool and wind the coil, controlling the winding speed to 2540m / min.
[0140] The expansion deformation control roller temperature is set at 188℃, the deformer temperature at 198℃, and the deformation pressure is set at 7.5 bar.
[0141] This stain-resistant yarn can be used to weave carpets made from stain-resistant yarn using shuttle looms.
[0142] Example 4
[0143] Stain-resistant yarn, including yarn using PA6 as the matrix material, also contains other components. The specific mass ratio of these other components to PA6 is as follows:
[0144]
[0145] The modified functional masterbatch preparation components include PA6 raw material. In this embodiment, 50% acrylic acid and 50% benzamide, which account for 50% of the molar mass of PA6 raw material, are weighed out for later use.
[0146] In the preparation of the modified functional masterbatch, acrylic acid is first fully dissolved in water and benzamide is dissolved in ethanol solution to prepare an acrylic acid solution and a benzamide ethanol solution with a concentration of 5%.
[0147] The specific process for preparing modified functional masterbatch is as follows:
[0148] Step 1: After filtration, wash with clean water and dry, add to a 5% acrylic acid solution, control the reaction temperature at 110℃, and react for 1.5 hours;
[0149] Step 2: After filtering again, wash with clean water and dry, add to a 5% benzamide ethanol solution, control the reaction temperature at 62℃, seal and pressurize at 1.6MPa, and react for 1.5h;
[0150] Step 3: After filtration, rinse with clean water and dry for later use.
[0151] The chemical equation for the reaction in step one of this embodiment includes:
[0152] CH2=CH-COOH+NH2-R-NH-CO(CH2)5-COOH→CH2=CH-CONH-R-NH-CO(CH2)5-COOH+H2O
[0153] Wherein: NH2-R-NH-CO(CH2)5-COOH is PA6; CH2=CHCOOH is acrylic acid.
[0154] The chemical equations for the reaction in step two include:
[0155] C6H5-CONH2+NH2-R-NH-CO(CH2)5-COOH→C6H5-CONH-R-NH-CO(CH2)5-COOH+NH3↑
[0156] Wherein: NH2-R-NH-CO(CH2)5-COOH is PA6; C6H5-CONH2 is benzamide.
[0157] The specific steps in the preparation process of stain-resistant yarn are as follows:
[0158] Step 1: Mix the prepared components into the hopper according to the proportions and stir until homogeneous. Use a screw extruder for melt extrusion and control the screw temperature settings as follows: 245℃, 285℃, 275℃, 273℃, 270℃, 268℃, 265℃.
[0159] Step 2: The extruded material is spun through the spinneret in the spinning box, cooled by side blowing, bundled and oiled, and the oil pump is controlled to apply 30% of the oil.
[0160] Step 3: Pre-network, set the pre-network pressure to 1.6 bar;
[0161] Step 4: Traction, control the ratio of the speed of the double rollers to the speed of the single roller to be 2.32;
[0162] Step 5: After expansion and deformation, cool and wind the coil, controlling the winding speed to 2550m / min.
[0163] The expansion deformation control roller temperature is set at 188℃, the deformer temperature at 198℃, and the deformation pressure is set at 7.5 bar.
[0164] This stain-resistant yarn can be used to weave carpets made from stain-resistant yarn using shuttle looms.
[0165] Comparative Example 1
[0166] The difference between Comparative Example 1 and Example 1 is that no perfluorooctane was added in Comparative Example 1, while all other conditions were the same.
[0167] Comparative Example 2
[0168] The difference between Comparative Example 2 and Example 1 is that no silicone oil was added in Comparative Example 1, while all other conditions were the same.
[0169] Comparative Example 3
[0170] The difference between Comparative Example 3 and Example 1 is that no heptadecafluorooctane-1-sulfonic acid was added in Comparative Example 1, while all other conditions were the same.
[0171] Comparative Example 4
[0172] The difference between Comparative Example 4 and Example 1 is that no modified functional masterbatch was added in Comparative Example 1, while all other conditions were the same.
[0173] Comparative Example 5
[0174] The difference between Comparative Example 5 and Example 1 is that Comparative Example 1 does not contain perfluorooctane, silicone oil, heptadecafluorooctane-1-sulfonic acid, or modified functional masterbatch; it only uses PA6 material, while all other conditions are the same.
[0175] Carpet sand threads were prepared according to Examples 1-4 and Comparative Examples 1-5, and square samples with a width of 1m were prepared. Their acid resistance and stain resistance were tested. The test method was as follows: Acid Blue 93 dye with a negative charge was used as the test reagent, and its dyeing rate was tested to determine its resistance to acid pollutants. The absorbance of the residual liquid and the original liquid after dyeing was measured by a UV-2600 ultraviolet spectrophotometer. The dyeing rate was calculated as (absorbance of residual liquid - absorbance of original liquid) / absorbance of original liquid × 100%.
[0176] Furthermore, the stain resistance test was conducted in accordance with the AATCC-175-2008 stain resistance test standard. The stain resistance was tested after 10 minutes of dyeing, 1 minute of rinsing with clean water, and drying. Level 10 indicates no staining and Level 1 indicates severe staining.
[0177] Furthermore, the breaking strength and breaking elongation were tested using a YG020 electronic single yarn tensile testing machine at a tensile rate of 25 cm / min, and the average value was taken after three tests.
[0178] The specific data is shown in the table below:
[0179] Example 1 36.5 9 2.34 Example 2 32.8 9 2.43 Example 3 31.4 9 2.61 Example 4 35.7 9 2.01 Comparative Example 1 50.6 6 2.23 Comparative Example 2 43.8 7 2.39 Comparative Example 3 58.2 5 2.44 Comparative Example 4 78.3 3 1.93 Comparative Example 5 89.4 2 1.56
[0180] The data in the table above shows that: when the content of modified functional masterbatch increases, its dyeing rate decreases, and it has good stain resistance. With the content of modified functional masterbatch exceeding the range, the dyeing rate will decrease slightly. Moreover, the breaking strength of the yarn is affected by step one, that is, the covalent bond formed by sulfonic acid solution and PA6 can improve the mechanical properties of the yarn.
[0181] Furthermore, the comparative data shows that perfluorooctane, silicone oil, heptadecafluorooctane-1-sulfonic acid, and the modified functional masterbatch all have anti-fouling effects when used individually. However, their anti-fouling effect is significantly reduced when combined synergistically, and the dyeing rate is significantly decreased. The main component affecting its breaking strength is sulfonic acid, primarily due to the chemical bonds it forms that improve structural stability. Therefore, if this yarn needs to be dyed, cationic dyeing should be used in conjunction with cationic dyes. Example 1 is a preferred embodiment, offering better cost performance and superior stain resistance compared to Example 3.
[0182] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely preferred examples and are not intended to limit the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of the present invention is defined by the appended claims and their equivalents.
Claims
1. A stain-resistant yarn, comprising yarn using PA6 as the matrix material, characterized in that: The stain-resistant yarn also contains other components, the specific mass ratio of which other components to PA6 are as follows: Modified functional masterbatch: 22-28%; Perfluorooctane: 2.5-4%; Organosilicon oil: 1.5-3%; Heptadecafluorooctane-1-sulfonic acid: 0.5-2%; The modified functional masterbatch preparation components include PA6 raw material, and sulfonic acid, acrylic acid and benzamide, accounting for 45-55% of the molar mass of PA6 raw material; In the preparation process of the modified functional masterbatch, sulfonic acid and acrylic acid are dissolved in water, and benzamide is dissolved in ethanol solution, all of which are prepared into sulfonic acid solution, acrylic acid solution, and benzamide ethanol solution with a concentration of 3-5%. The specific process for preparing the modified functional masterbatch is as follows: Step 1: Add PA6 to a 3-5% sulfonic acid solution, add trisodium phosphate or ammonium sulfate as a catalyst, control the reaction temperature at 80-100℃, and react for 2-4 hours; Step 2: After filtration, wash with clean water and dry, add to a 3-5% acrylic acid solution, control the reaction temperature at 100-120℃, and react for 1-2 hours; Step 3: After filtering again, wash with clean water and dry. Add to a 3-5% concentration of benzamide ethanol solution, control the reaction temperature at 60-70℃, seal and pressurize at 1.2-1.8MPa, and react for 1-2 hours. Step 4: After filtration, rinse with clean water and dry for later use.
2. The stain-resistant yarn as described in claim 1, characterized in that: The chemical equation for the reaction in step one is: NH2-R-NH-CO(CH2)5-COOH+HOOC-CH2-CH2-SO3H→NH2-R-NH-CO(CH2)5-COO-SO3H+H2O Wherein: NH2-R-NH-CO(CH2)5-COOH is PA6; HOOC-CH2-CH2-SO3H is sulfonic acid.
3. The stain-resistant yarn as described in claim 2, characterized in that: The chemical equation for the reaction in step two includes: CH2=CH-COOH+NH2-R-NH-CO(CH2)5-COOH→CH2=CH-CONH-R-NH-CO(CH2)5-COOH+H2O or: CH2=CH-COOH+NH2-R-NH-CO(CH2)5-COO-SO3H→CH2=CH-CONH-NH2-R-NH-CO(CH2)5-COO-SO3H+H2O Wherein: NH2-R-NH-CO(CH2)5-COOH is PA6; CH2=CHCOOH is acrylic acid.
4. The stain-resistant yarn as described in claim 3, characterized in that: The chemical equation for the reaction in step three includes: C6H5-CONH2+NH2-R-NH-CO(CH2)5-COOH→C6H5-CONH-R-NH-CO(CH2)5-COOH+NH3↑ or: C6H5-CONH2+NH2-R-NH-CO(CH2)5-COO-SO3H→C6H5-CONH-R-NH-CO(CH2)5-COO-SO3H+NH3↑ Wherein: NH2-R-NH-CO(CH2)5-COOH is PA6; C6H5-CONH2 is benzamide.
5. The stain-resistant yarn as described in claim 4, characterized in that: The specific steps in the preparation process of the stain-resistant yarn are as follows: Step 1: Mix the prepared components into the hopper according to the proportions and stir until homogeneous. Use a screw extruder for melt extrusion and control the screw temperature settings as follows: 245℃, 285℃, 275℃, 273℃, 270℃, 268℃, 265℃. Step 2: The extruded material is spun through the spinneret in the spinning box, cooled by side blowing air, bundled and oiled, and the oil pump is controlled to apply oil at 25-35%; Step 3: Pre-network, set the pre-network pressure to 1.5-1.8 bar; Step 4: Traction, control the ratio of the speed of the double roller to the speed of the single roller to be 2.28-2.35; Step 5: After expansion and deformation, cool and wind the coil, controlling the winding speed to be 2520-2550 m / min.
6. The stain-resistant yarn as described in claim 5, characterized in that: The expansion deformation control roller temperature is set at 185-190℃, the deformer temperature at 198-200℃, and the deformation pressure at 7.4-7.6 bar.
7. A carpet made of stain-resistant yarn as described in any one of claims 1 to 6, characterized in that: The aforementioned stain-resistant yarn can be used to weave carpets made from stain-resistant yarn using a shuttle loom.
Citation Information
Patent Citations
High molecular weight acrylic anti-stain treatment for nylon carpet
CN1050417A
Anti-fouling nylon carpet yarn and preparation method thereof
CN116145297A
Production of polyamide of increased terminal carboxyl group content
JP1989236238A